2019
DOI: 10.1021/acs.jafc.8b07011
|View full text |Cite
|
Sign up to set email alerts
|

Thiamethoxam Metabolism and Metabolic Effects in Cell Suspension Culture of Tea (Camellia sinensis L.)

Abstract: Thiamethoxam (TMX) has already been proven to have a physiological effect in plant tissue or cell expect for the insecticidal activity. In our previous study, TMX was verified to be metabolized by tea cells in either a suspension culture or tea plant into several metabolites. Here, tea cell suspension cultures were treated for 45 days to investigate the metabolite effects in both the tea cells and the culture supernatants by nontargeted metabolomics. Using multivariate analysis (PCA and OPLS-DA), all treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
1
6
0
1
Order By: Relevance
“…The metabolic rate of TMX (30% SC, 1.5 X) in tea plants was consistent with that of our previous research, 13,28 the longer the treatment time, the lower the content of TMX in the tea plants with the higher degradation rate. However, the degradation rate of different concentrations of TMX in tea cell suspension cultures was lower than 50% at 75 days in our previous study, 13 while the degradation rate of TMX in tea plant reached about 93% at 7 days (Fig. 1B).…”
Section: Metabolism Of Tmx In Tea Plantsupporting
confidence: 91%
See 2 more Smart Citations
“…The metabolic rate of TMX (30% SC, 1.5 X) in tea plants was consistent with that of our previous research, 13,28 the longer the treatment time, the lower the content of TMX in the tea plants with the higher degradation rate. However, the degradation rate of different concentrations of TMX in tea cell suspension cultures was lower than 50% at 75 days in our previous study, 13 while the degradation rate of TMX in tea plant reached about 93% at 7 days (Fig. 1B).…”
Section: Metabolism Of Tmx In Tea Plantsupporting
confidence: 91%
“…In addition to the direct interaction of TMX with certain enzymes, TMX may act as a signaling molecule regulating the gene expression activity, especially genes in certain metabolic pathways. 13 This work provided a theoretical basis for the interactions between plants and pesticides as well as the effect of pesticide application on tea quality and environmental risk assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, only three metabolites (TMX-dm, CLO, and C 5 H 8 O 2 N 3 SCl) were identified in the pepper plant and cultivated soil. However, Ge et al 29 reported that TMX could produce 235 metabolites inside tea plant cells and 163 metabolites in culture supernatant. WHO/FAO 30 reported that twenty-two TMX metabolites were detected from the excreta of rats.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Sua molécula também mostra efeitos positivos na fisiologia e metabolismo vegetal para muitas culturas, como feijão (Cataneo et al 2010), trigo (Macedo and Castro 2011), arroz (Macedo et al 2013a;Lanka et al 2017), milho (Afifi et al 2015), soja (Cataneo et al 2010;Bortoletto et al 2017) e pastagens (Macedo et al 2013b) (Ge et al 2019). Devido aos efeitos proeminentes no vigor das plantas, ganhos no influxo de água, transporte de íons ou ativando o metabolismo primário e secundário, essa molécula foi classificada como bioativador (Macedo et al 2013b, a).…”
Section: Introductionunclassified